Kepercayaan Diri dengan Tingkat Kecemasan pada Mahasiswa Tingkat Akhir dalam Mengerjakan Skripsi di Institut Kesehatan Immanuel Bandung - Marbun, Kristin Arta Feronica; Siagian, Ira Ocktavia; Sinaga, Herwinda (STIKES Ngesti Waluyo, 2023)
Anxiety in facing and working on thesis is a worried behaviour that makes students uncomfortable. This discomfort makes it difficult for students to concentrate in facing the thesis. In facing and doing the thesis, it is necessary to have self-confidence in the form of a feeling of individual confidence in their abilities. This study aims to analyse the relationship between self- confidence and anxiety levels in final year students working on their thesis at Immanuel Health Institute Bandung. This type of research used quantitative research with correlational analytical through cross sectional approach. The sampling technique used total sampling of 75 respondents. Data were measured using the Lauster questionnaire with a reliability value of 0.946 and a validity of 0.377, and the Zun self- rratin Anxiety Scale (ZSAS) questionnaire with a reliability value of 0.829 and a validity value of 0.918. Univariate analysis was conducted using frequency distribution and bivariate analysis using the Spearman Rank test. The results of data analysis obtained that there is a significant relationship between self-confidence and anxiety in final year students in working on the thesis, which is indicated by the results of the correlation coefficient rxy=-0.445 with a p-value of 0.000 <0.05. This means that the higher the self-confidence, the lighter the level of anxiety is, or vice versa. This research is expected to provide information about the importance of having self-confidence in students to minimise their anxiety when working on thesis, therefore students can prepare themselves properly.